Characterization of the age-hardening behavior of a precipitation-hardenable austenitic steel - Satyanarayana D.V.V.; Malakondaiah G.; Sarma D.S. (My University, 2025)
This paper describes the age-hardening behavior and microstructural features of a precipitation-hardenable austenitic steel. It has been found that the optimum heat treatment for the current alloy, in terms of strength, involves solution treatment at 1473 K for 1 h followed by aging at 973 K for 5 h. The precipitating phase, leading to significant strengthening in this alloy, has been identified as NiAl. The NiAl precipitates are ordered with a CsCl-type crystal structure and exhibit a plate-like morphology. These precipitates have been found distributed in two orientations and show a Kurdjmov-Sachs orientation relationship with the matrix. The alloy retains high strength up to about 700 K, beyond which there is a significant drop in strength. © 2001 Elsevier Science Inc. All rights reserved.